Risiko Litigasi Memoderasi Pengaruh Kepemilikan Manajerial dan Ukuran Perusahaan Terhadap Konservatisme Akuntansi - Wahidah Nursafiyah; Zaky Machmuddah (Accounting Profession Journal (APAJI), 2025)
The purpose of this study is to analyze how managerial ownership and firm size affect accounting conservatism with the moderating variable being litigation risk. The sample includes 170 non-cyclical consumer sector companies on the IDX for the period 2020-2024, selected using the purposive sampling method. Multiple linear regression are used as the analysis methods. The findings show a negative and insubstantial impact for managerial ownership, while firm size has a positive and substantial impact on accounting conservatism. The relationship between managerial ownership or firm size and accounting conservatism is not strengthened or weakened by litigation risk. The implication of this research is the importance of accounting conservatism for companies towards corporate sustainability.